Effect of various inducing agents on bacteriocin (klebocin) production by Klebsiella pneumoniae - Chhibber, S; Vadehra, D V (Folia microbiologica, 1987)
The influence of various inducing agents on growth, synthesis and release of klebocin by Klebsiella pneumoniae was studied. A significant level of klebocin was detected only after induction. The highest level of klebocin was achieved with mitomycin C followed by rifampicin and polymyxin B. Chloramphenicol and UV irradiation did not show any effect on klebocin production. Maximum klebocin release occurred after 8 h of induction with all the agents. Concentration of mitomycin C did not show any significant effect on klebocin production.
Keywords: Chloramphenicol; mitomyciny; Klebsiella pneumoniae; polymyxin B; Ultraviolet Rays; Mitomycin; Rifampin; Mitomycins; Bacteriocins; bakteriociny; ultrafialové záření; Polymyxin B; rifampin; chloramfenikol; mitomycin